Study the Relationship of PCSK9 Gene Polymorphism and PCSK9 Protein on Serum Bad Cholesterol and Risk of CVDs in Iraqi Patients - Rafid A. Abdulkareem; Anas Abdaljaleel Khaleel (Indian Journal of Forensic Medicine & Toxicology, 2021)
Cardiovascular disease responsible for number 1 of death worldwide. Many genetic and environmentalfactors influence the development of CVDs. PCSK9 protein responsible for degradations of LDLRwhich lead to increase blood level of bad cholesterol. Gain of function mutation in PCSK9gene result inhypercholesterolemia and loss of function lead to hypocholesterolemia. Aim of this study: to investigatethe polymorphism of rs775278198 of PCSK9 gene and serum level of PCSK9 with their effect on LDL-Clevel in CVDs patients. Materials and methods: a common SNP PCSK9 gene was studied using Real-Time PCR and technique to show association between PCSK9 SNP with risk of developing CVDs. fifty ofcardiovascular diseases patients who were clinically diagnosed by physicians and fifty apparently healthyindividuals were conducted within this study. Blood samples were collected from all subjects after overnightfasting. Genomic DNA was extracted from blood samples and analyzed for rs775278198 SNP in PCSK9gene with specific primers and probes using Real-Time PCR technique. Also, serum levels of PCSK9 wereevaluated using Elisa kit supplied by Bioassay Technology Laboratory. In addition LDL-C levels weremeasured by lipid profile test kit (CHOL2) supplied by Roch. Identification of PCSK9 SNP polymorphismand PCSK9 serum levels with LDL-C levels in this study success percentage of the methods. Results: inReal Time PCR, CVDs patients appeared the TT (20 vs 4, OR=6, p=0.028) genotypes were significantlyhigher in patients when compared to controls group (20 vs 4%, OR=6, P=0.028) .In comparison of theserum levels of PCSK9 in CVDs patient were higher than PCSK9 serum levels in controls group (p value=f0.000005) at the same time there is a positive relationship between PCSK9 serum levels and LDL-C levelsas measured by Pearson Correlation.